In situ inspection of ultra durable concrete using electrical resistivity technique - Lim, Darren Tze Yang (2013)
In today’s rapid construction, a reliable method for quick evaluation of concrete quality during construction is very important. The compressive strength of concrete has been used to evaluate the mechanical properties of concrete; however compressive strength may not represent the durability of concrete. Rapid Chloride Migration Test (RCMT) and electrical resistivity can be used to evaluate the durability of concrete. Obtaining the coefficient of chloride diffusivity from RCMT usually requires a testing duration of 24 hours or less for normal strength concrete. With the inclusion of supplementary cementitious materials and lower water/cementitious ratio to achieve a higher strength and more durable concrete, testing of the concrete becomes an elaborate affair which might takes at least four to five days of testing. Electrical resistivity technique has been used to evaluate the quality of normal strength concrete. However the suggested classification of concrete quality is not applicable to ultra durable concrete. In this work, the effectiveness of using the concrete resistivity test results from electrical resistivity technique is studied. With the use of direct and four points Wenner probe methods, the concrete resistivity results were obtained and compared with the coefficient of chloride diffusivity from RCMT. Six mixes of three different grades with the inclusion of 30% granulated ground blast-furnace slag and 10% undensified silica fume were designed and tested; and high correlation coefficients (>0.94) for all the mixes were achieved. This represents the effectiveness of using the electrical resistivity technique to carry out fast and accurate in-situ test to determine the quality of the ultra durable concrete.